Quantitative assessment of myocardial blush grade in patients with coronary artery disease and in cardiac transplant recipients - Hofmann, Nina; Dickhaus, Hartmut; Katus, Hugo; Korosoglou, Grigorios (World journal of cardiology, 2014)
Quantitative assessment of myocardial blush grade in patients with coronary artery disease and in cardiac transplant recipients
Gesehen am 10.02.2021